Dis:connectivity and globalisation: concepts, terms, practices - Balme, Christopher; Dogramaci, Burcu; Wenzlhuemer, Roland (De Gruyter Oldenbourg, 2025)
Globalisation is one of the most contested concepts of our time. From its promise of borderless flows of people, goods, and finance in the 1990s, it embodies today almost the opposite: deglobalisation, as tariffs are erected, borders heavily policed, anti-migration regimes enforced and sanctions levied. This ‘disconnect’ between promise and realisation is the subject of this volume. In almost forty short essays and an introduction, it explores key concepts that illuminate processes of globalisation from a dis:connective perspective, which highlights the role of delays and detours, interruptions, resistances and absences as constitutive of globalisation. The volume proposes rethinking globalisation by redefining the terminology we use to describe and analyse it.